DNA metabarcoding and phytochemical analysis of plants consumed by banded langur (presbytis femoralis) in Johor - Haris, Norhidayah (2021)
Banded langur (Presbytis femoralis) is a leaf-eating monkey that is now classified as vulnerable in IUCN Red List and to date, there are less than 500 individuals of P. femoralis that can be observed in some fragmented areas in Johor. Currently, banded langur is facing a problem in which there is no comprehensive record of their plants’ selection and there is no information on phytochemical compositions in their diets. This data is crucial for their conservation plan along with solving the human-wildlife conflict, but it is very challenging to identify the plants consumed by them through direct observations. Thus, the objectives of this study are to investigate the plant selection by P. femoralis based on a DNA metabarcoding approach using the trnL region of chloroplast DNA and to identify the phytochemical compounds in the selected plant species consumed for bioprospecting purposes. Through the sequencing method of four faecal samples collected, a total of 140611 operational taxonomic units (OTUs) were detected which were assigned to 38 families and 71 genera of plants. The plants from the family of Fabaceae (3.03%) contributed to the most plant food consumed, followed by the family of Euphorbiaceae (2.63%) and Malvaceae (1.10%). As for the phytochemical analysis of three selected plant species, namely, Spathodea campanulata, Talipariti tiliaceus and Xylocarpus granatum, most of the selected plants have no or low amount of flavonoid and alkaloid, and all the leaves samples are rich in phenolic, saponin and tannin than the flower sample. Then, a total of nine tentative assignments of chemical constituents were detected in the selected plant species through LCMS/MS technique. Each of the chemical compounds acquired has its potential bioactive properties. Overall, the data gained through this study may provide important insights for the banded langur conservation management. Consequently, the information on the bioactive compounds can certainly provide a piece of new knowledge on the usage of the plants, especially for self-medication among primate which may indirectly help in providing a new pathway for the development of useful drugs in the medicinal world.